Sustainable Pharma: The Need, Current Status and Mission for the Future - Agrawal, Madhav; Bansal, Alka; Khandelwal, Vishnu Kumar; Bansal, Nidhi (Scripta Medica, 2024)
’’Good health and well-being" (SDG3) are one of the 17 integrated sustainable development goals (SDG) adopted by the United Nations in 2015. When it comes to health and well-being, pharmaceuticals play a vital role. Pharmaceutical waste and contaminants of emerging concern (CEC) produced during the manufacturing, supply, usage and disposal of drugs, chemicals and personal care products can significantly affect the environment. Some serious global problems have been attributed, at least partly, to the prevalent practices in this sector. With increased awareness, regulations and corporate environmental responsibility, the pharmaceutical industry is making efforts toward sustainability through measures like green production, green technology, improved supply chains, collaborations and strategic partnerships. However, the need is still felt for additional measures to be incorporated into the practice like a circular economy, based on the 4Rs (reduce, recycle, reuse, recover); Artificial Intelligence (AI) can be used to recognise the best way to obtain maximum yield with minimum cost from available resources in an environment-friendly manner for the benefit of society; encouraging the use of renewable energy and promoting research focused on environmental supportive and profitable measures. The journey towards sustainable pharma is complex and requires collaboration across the entire value chain from all the stakeholders, but the benefits to society, the environment and the industry are profound and far-reaching.